The role of intravitreal chemotherapy for retinoblastoma - Fairooz P Manjandavida; Carol L Shields (Indian Journal of Ophthalmology, 2015)
Targeted therapy in retinoblastoma (RB) is widely accepted as the current management tool with an aim of increasing drug availability at the tumor location. Inevitably the effect is several times higher compared to systemic delivery of chemotherapeutic drugs and carries less systemic toxicity. Despite tremendous advancement in saving life, eye salvage in advanced RB especially with active vitreous seeds remains a challenge. The hypoxic environment of the vitreous and reduced vitreous concentration of the drugs delivered makes these tumor seeds resistant to chemotherapy. Direct delivery of chemotherapeutic drugs into the vitreous cavity aids to overcome these challenges and is progressively being accepted worldwide. However, intraocular procedure in RB was abandoned due to high risk of extraocular tumor dissemination. Recently, the forbidden therapeutic technique was re-explored and modified for safe use. Although eye salvage rate has tremendously improved after intravitreal chemotherapy (IVitC), retinal toxicity, and vision salvage are yet to be validated. In our preliminary report of intravitreal melphalan in 11 eyes, we reported 100% eye salvage and 0% recurrence with an extended 15 months mean follow-up. In this review, we analyzed published reports on IVitC in RB via PubMed, Medline, and conference proceedings citation index, electronic database search, without language restriction that included case series and reports of humans and experimental animal eyes with RB receiving IVitC.